Autologous fat tissue grafting improves pulmonary healing after laser metastasectomy. Issue 12 (December 2017) - Furia, Simone; Cadenelli, Pierfrancesco; Andriani, Francesca; Scanagatta, Paolo; Duranti, Leonardo; Spano, Andrea; Galeone, Carlotta; Porcu, Luca; Pastorino, Ugo
Abstract: Background: Extensive clinical experience has demonstrated the potential usefulness of autologous fat tissue (AFT) graft in tissue reconstruction, repair or regeneration. In the present study, we evaluated the feasibility and safety of AFT in the repair of surgically injured lung surface. Methods: Eighty consecutive procedures of pulmonary metastasectomy by laser precision resection, were performed in 66 patients between March 2010 and December 2012. In the first 20 procedures, AFT graft was applied on the wounded pulmonary surface without closure of parenchymal surface. The following 40 procedures were carried on without AFT (20 leaving the resection margins open and 20 closing the resection margins with a running suture). In the remaining 20 procedures, AFT was applied and the resection margins closed. The efficacy of this technique was evaluated by comparing the AFT group with the non-AFT group, with respect to prolonged alveolar air leakage (PAAL), time to drain removal, length of hospital stay, and patient survival at four years. Results: The occurrence of PAAL was lower in the AFT group as compared to non-AFT group (17.5% versus 42.5%, p = 0.027), and median time to drain removal shorter (4 versus 6 days respectively, p = 0.016). Overall 4-year survival was 70% for AFT group, and 59% for non-AFT group (p = 0.34). Conclusions: This prospective cohort observational study demonstrated the feasibility and safety of AFT pulmonary grafting after laser metastasectomy. AFT graft improved pulmonary healing, by reducing the incidence and severity of PAAL. Moreover, there was no evidence of tumor promotion in the metastatic setting, with a similar overall survival at 4 years.